81.7k views
5 votes
Please Read the Attachment below

Please Read the Attachment below-example-1

1 Answer

3 votes

Answer:

Explanation:


(a -30y)/(a^2 -100y^2) - (10y)/(10ay -a^2)


=(a-30y)/(a^2 -(10y)^2) - (10y)/(-a(a -10y))\\\\=(a-30y)/((a -10y)(a+10y)) + (10y)/(a(a -10y))\\\\=(a(a-30y) +10y(a+10y))/(a(a -10y)(a+10y)) \\\\=(a^2 - 30ay +10ay +100y^2)/(a(a-10y)(a+10y))\\\\=(a^2 - 20ay +100y^2)/(a(a-10y)(a+10y))\\\\=((a-10y)^2)/(a(a-10y)(a+10y))\\\\=((a-10y))/(a(a+10y))

User Brejuro
by
4.7k points